(untitled) (Journal of Parents and Teachers, 2025)
The article refers to two stories of two different grandmothers, where they share experiences, they have gone through, and both realize that today’s youth live a life centered around consumerism and the notion that nothing is ever enough. Additionally, the article includes a series of questions that prompt reflection on the role grandmothers play in families and whether the care they provide is beneficial or not.